Evaluación del control interno a través del Modelo COSO ERM y su incidencia en los riesgos del GAD Parroquial Rural San Luis, período 2020. - Yuquilema Achache, Henry Stalin (2023)
One of the most crucial procedures that must be used in an organization is the evaluation of internal control. Through this review, it is possible to determine whether processes and resources have been used appropriately, and through the internal control analysis, it is possible to identify, evaluate, and establish a framework of risk-reduction strategies. The aim of the current study was to assess internal control using the COSO ERM model and its impact on risk management for the GAD Parroquial Rural San Luis, period 2020. The study started with the identification of the research problem, the establishment of general and specific objectives, and the application of the COSO ERM 2017 internal control questionnaire as a data collection tool. Each component was evaluated using its corresponding guiding principles, and the theoretical aspect was supported by both bibliographical and field research. As a result of the analysis, it was possible to determine that the GAD does not evaluate internal control, that there is no risk matrix that identifies risk and its control mechanism, that periodic staff training is not conducted, that the information system does not meet the GAD's requirements, and that the critical point within the entity is the operational level where decisions are made.